2020
DOI: 10.1177/0391398820975408
|View full text |Cite
|
Sign up to set email alerts
|

Venovenous ECMO treatment, outcomes, and complications in adults according to large case series: A systematic review

Abstract: Background: Venovenous extracorporeal membrane oxygenation (VV ECMO) has gained popularity for the treatment of refractory respiratory failure during and after the 2009 influenza pandemic, and still represents a precious therapeutic resource for severe novel coronavirus 2019 infection. However, most of the published studies are small case series, and only two randomized trials exist in literature. Aim: Aim of this systematic review is to describe trends in VV ECMO treatment outcomes according to large studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Veno-venous (V-V) ECMO is an invasive technique that oxygenates the blood and removes CO 2 while the failing lung is put at rest and is given time to recover. Management of ECMO patients is generally performed in tertiary care referral centers as it requires expertise in treatment of refractory respiratory failure and severe ARDS 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Veno-venous (V-V) ECMO is an invasive technique that oxygenates the blood and removes CO 2 while the failing lung is put at rest and is given time to recover. Management of ECMO patients is generally performed in tertiary care referral centers as it requires expertise in treatment of refractory respiratory failure and severe ARDS 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Of note, several ECMO strategies may be used under the expertise typical of cardiac centers (venovenous or venoarterial; percutaneous or central cannulation), and this should be considered in relation to the clinical conditions, including the presence of RV dysfunction. However, these strategies expose patients to the risks of cannulation and systemic anticoagulation, 72 and the higher risk of bleeding and transfusions when systemic anticoagulation is started in the perioperative period of cardiac surgery should be considered.…”
Section: Ards In Cardiac Surgery Patients: Treatment Optionsmentioning
confidence: 99%
“…73,74 Kim and colleagues aimed to analyze temporal trends, complications, and outcomes by performing a systematic review of a large population of VV-ECMO patients with ARDS. 75 The authors identified 33 studies and included 12 860 patients in their analysis. The average VV-ECMO patient was young (46.3 ± 17.4 years old), likely male (63% of patients), and most likely to have pneumonia as the cause of ARDS (37% undifferentiated pneumonia, 7% H1N1 pneumonia).…”
Section: Mechanical Circulatory Support: Honing Indications and Understanding Outcomesmentioning
confidence: 99%